Halide perovskite metasurfaces with tunable exciton-polariton electroluminescence - Wang, Yutao (2023)
We report strong coupling between excitons and photonic bound states in the continuum in electrically-driven perovskite metatransistors. We show tunability of electroluminescence directivity by drain-source voltage and polarization control through metasurface design.